Reimplementasi Hukum Pidana Dalam Aspek Kepemilikan Hak Atas Tanah - Suhartati - (Jurnal Hukum PRIORIS, 2014)
The outgrowth of corruption cases in Indonesia both quantity and quality has involving several business sectors such as land sectors. The complexity of land sector problems dealing with administrative law, civil law, and criminal law directing as the object of corruption cases. Considering the land-ownership as one of valuables assets which has economical value could create legal problems within individual, corporation, or state. The precious value of land even causing some actions with the state loss as a negative impact. Through some cases in Indonesian, several actions related with transferring land-ownership even indicated as corruption crime due to state loss impact. Regarding the aforementioned legal phenomenon, this article aim to explore how the land-ownership matters could be implied as corruption crimes and how the corruption criminal law could be implemented.This article is analysing that several legal actions related with land-ownership of state own enterprises or private corporation are not directly pointed as corruption crimes, even though there are state loss inside land-ownership. Corruption crime will be defines upon the occurrence of primary elements based on Article 2 or Article 3 Indonesian Act Number 31 Number 1999 jo Indonesian Act Number 20  Year 2001. Especially the unlawfulness element shall be proven in every act which has purpose of self or corporate enrichment. Reimplementation of corruption criminal law by applying formal unlawfulness element and material unlawfulness element with negative function are needed to the efficacy of combating corruption acts and to avoid over criminalization.